Law of Credit and Security - LOO, Wee Ling (Institutional Knowledge at Singapore Management University, 2012)
The 'Law of Credit and Security' is more than an update of the original work published in 1999 under the title of 'Finance Law'. In this new edition, the reader is eased into an understanding of the role of a banker in relation to its customer, the life cycle of a loan transaction, the practical, commercial and legal considerations which go into the negotiation of the financial package and the methods in which lenders protect their interest through carefully drafted contractual terms. It also introduces the multi-varied methods of obtaining financing in the course of a business and the kinds of security or quasi-security interests that may be created over different assets or given by an individual in favour of the financier; with basic legal principles and key legal issues highlighted. The reader will then be taken through the legal remedies available to a financier should a borrower of a debtor default. This title is an enhanced resource text for the non-law student pursuing a course in the law of credit and security in any tertiary institution. Law students and the legal professional may also find it useful for a basic understanding of the topics covered and as a guide for further research into the subject.